Local correlation-based transition model for aerodynamic flows in wide speed range - Hexia Huang; Zaijie Liu; Huijun Tan (Engineering Applications of Computational Fluid Mechanics)
A local correlation-based transition model is developed for aerodynamic flows in a wide speed range. New localized methods for the momentum-thickness Reynolds number are introduced for constructing local transition indicators. New transition correlations are developed to detect transition in high-speed flows, containing the influences of freestream turbulence intensity, pressure gradient, nose-tip bluntness, and compressibility. An intermittency factor transport equation is established and coupled with the [Formula: see text]–[Formula: see text] shear-stress transport turbulence model. The new model is validated against several available experiments on subsonic to hypersonic flows, including flat plates, airfoils, and straight or flared cones. The results demonstrate the model's ability for engineering transition predictions in a reasonably wide range of flow conditions.